“Andung” as Tobanese Oral Tradition : Melodic Form and Contours - Jubilezer Sihite; Septian Panjaitan (Universitas Cokroaminoto Palopo, 2021)
This study deals with the melodic formula and contours of expressed Andung during mourning ceremony in Toba Batak (based on the Malm theory). The objectives were to to find out the types melodic form and type of contours used in Andung. This research used descriptive qualitative design because it is only focused on the culture context of Andung, and also the data was also in the form of utterances. There are five types of melodic form ; repetitive, interative, reverting, stropic, progressive and five types of contours applied in Andung, they are ascending, descending, pendulous, terraced, static. It is found that stropic and progressive are the most dominantly applied, besides ascending and descending are the most dominantly practiced in Andung because the lamenters had relationship with the individual experience in terms.